Assessment of S1 progenies in two diverse populations of fennel (Foeniculum vulgare Mill.) - Singhania, V V Singh, E V D Sastry, D L (Journal of Spices and Aromatic Crops, 2004)
An investigation was conducted at Jobner (Rajasthan) to estimate variability, heritability and expected selection gain among S, progenies generated from RF-125 and UF-143 populations of fennel (Foeniculum vulgare). The inter-family variance was higher in comparison to intra-family variance in both the populations for most of the characters studied. The estimates of heritability (narrow sense) were high only for plant height in RF-125. For rest of the characters, the heritability was medium to low. The expected genetic gain was medium to low in both the populations and was highest in umbels plant-1 in RF-125. The study suggests that significant inter family variance is still present in these populations which can be exploited.